Effectiveness Service Public In Increase Child Identity Card Program at the Population Service and Civil Registration of Kuningan Regency - Liza Cristianli Maharani; Yanto Heryanto (Athena: Journal of Social, Culture and Society, 2026)
The importance of effective public services will be discussed within the Child Identity Card (KIA) program carried out by the Population and Civil Registration Office of Kuningan Regency. The problems analyzed concern the lack of effectiveness of the provision of KIA services promptly due to the technological limitations of the system, insufficient human resources, and lack of public understanding about the need for KIA. The purpose of this research is to provide a demonstration of the effectiveness of KIA services using the method proposed by Siagian (as cited in Nashar, 2020) based on three aspects: timeliness, accuracy, and service style. These results show that the factor of time is still not fully efficient, even though there are SOPs that range from 1 hour to 24 hours, as it is still dependent on the Department of Population and Civil Registration. on changes in the SIAK system, network problems, geographic factors, and human resources. Nevertheless, when it comes to the matter of accuracy and delivery styles, one may notice some very positive aspects here, because it may include such things as comprehensive procedures for issuance, staff attitude, the utilization of digital services, and good and fair services. As a consequence, one may note that there are a lot of ways to enhance the efficiency of KIA. Thus, future research may consider public satisfaction as one of its major elements.